2005
DOI: 10.1002/lsm.20214
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of oral verrucous hyperplasia and oral leukoplakia with topical 5-aminolevulinic acid-mediated photodynamic therapy

Abstract: We conclude that complete regression of OVH lesions can be achieved by less than six treatments of topical ALA-PDT once a week. Although the response of OL lesions to the topical ALA-PDT is not as good as the response of OVH lesions to the same therapy, all OL lesions can have at least PR after eight treatments with the topical ALA-PDT twice a week. In addition, OL lesions treated twice a week have a significantly better clinical outcome than OL lesions treated once a week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 29 publications
3
117
0
9
Order By: Relevance
“…The mean size score for 12 leukoplakia lesions before therapy was 1.82 ± 0.89 and 1.16 ± 0.98 after therapy, this difference was significant statistically (P < 0.001). The present study results obtained correlated with the study conducted by Kubler et al, 17 Kubler et al, 19 Tsai et al, 22 and Chen et al, 29 where in the study conducted by Kubler et al, 17 6 leukoplakia cases were treated by topical application of 5-ALA (20% cream) and irradiated with argon-pumped dye laser resulting complete response in 2 (33.33%) patients, partial response in 3 (50.0%) patients and no response in 1(16.66%) patient. In the other hand, our results are inconsistent with the results of the study conducted by Fan et al, 18 Kubler et al 19 and Franco.…”
Section: Discussionsupporting
confidence: 92%
“…The mean size score for 12 leukoplakia lesions before therapy was 1.82 ± 0.89 and 1.16 ± 0.98 after therapy, this difference was significant statistically (P < 0.001). The present study results obtained correlated with the study conducted by Kubler et al, 17 Kubler et al, 19 Tsai et al, 22 and Chen et al, 29 where in the study conducted by Kubler et al, 17 6 leukoplakia cases were treated by topical application of 5-ALA (20% cream) and irradiated with argon-pumped dye laser resulting complete response in 2 (33.33%) patients, partial response in 3 (50.0%) patients and no response in 1(16.66%) patient. In the other hand, our results are inconsistent with the results of the study conducted by Fan et al, 18 Kubler et al 19 and Franco.…”
Section: Discussionsupporting
confidence: 92%
“…The fluorescence intensity in the malignant tissue reaches a maximum between 1 and 2 h after ALA application. 6,17,22,24 Numerous studies have shown that violet laser excitation induces both autofluorescence and ALA-induced fluorescence. 15,16,[18][19][20] The wavelength of the former is in the green-to-red range, whereas that of the latter falls mainly in the red band.…”
Section: Basis and Development Of The Image Processing Methodsmentioning
confidence: 99%
“…Pode ser dividida em indicações gerais (Quadro 11) e dermatológicas, e esta em oncológica e não oncológica. A TFD-ALA associada ao LED tem apresentado bons resultados no tratamento de lesões orais principalmente lesões de displasia da mucosa e carcinoma in situ 250,355 , carcinoma verrucoso extenso e de leucoplasia oral 356,357 .…”
Section: Indicações Da Terapia Fotodinâmicaunclassified